Zmierzch interakcji instruktywnej. W stronę autonomii w dialogu rodzice – nauczyciele - Gulczyńska , Anna (Studia Edukacyjne, 2019)
The theoretical background of the parents–teachers relation is systemic approach. It is the basis for a critical analysis of the pedagogization idea, treated as instructive interaction. Expert interaction between parents and teachers was proposed. The proposal of those relations based on the healing orientation by K. Ludewig was presented at the end of the article. The practical aim is to generate reflection and eventually activities to implement the particular suggestions in teachers’ pedagogical work.